ALTERNATIF PEMAKAIAN JENIS-JENIS BAHAN PENGISIAN (FILLER) PADA CAMPURAN ASPHALT CONCRETE HOT MIX - Ngurah Tjerita, A.A. Ketut; Suparsa, I Gusti Putu (Jurnal Ilmiah Teknik Sipil; Vol. 9, No. 1 Januari 2005, 2012)
The safety and comfortable of the user of road is determined by quality of its surface course which can be stated by the index value of its surface. The use of Hot Rolled Sheet (HRS) as a surface course is very famous in Indonesia. So it is a need to improve its quality. Because of the lack of its filler at a natural aggregation and the limit of production of stone ash from the stone crusher, it is required an endeavour to find out the alternative filler which can replace the stone ash functions in the Hot Rolled Sheet mixture. For this reason, it will be tried to use the ash of limestone and “Portland” cement as alternative filler. A research has been undertaken in a laboratory by making a specimen as a sample and treatment to different fillers, a various asphalt quantity and aggregation of gradation which fulfill the specification from Bina Marga. The result shows that by different fillers will make a different characteristic of mixture, but on certain asphalt quantity the three treatments that is filler of stone ash, ash of limestone and “Portland” cement, still in line with the specification from Bina Marga.
Keywords: alternative used, filler, asphalt concrete hot-mix